ANALISIS FAKTOR PENGARUH ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK DALAM PERKARA REKLAMASI TELUK JAKARTA - Hany Mora Yuniavenda Simamora; Faza Rayhan Rizaldy; Gilberth Abednego (Peneliti.net, 2023)
The general principles of good governance (AAUPB) have been applied as a guideline in organizing an ideal government in order to create prosperity for every citizen, especially in the case of the Jakarta Bay reclamation. The method used in this study is a statutory approach as well as a conceptual approach by observing and analyzing literary sources and data from reports related to the cases discussed. The results of this study indicate that the existence of AAUPB is not merely a regulation, but must be implemented in a real way in a government. The general principles of good governance should become regulations that can become a tool to ensure the implementation of reclamation in Jakarta Bay must be carried out based on the AAUPB by obtaining permits from various parties, especially the authorities in the reclamation area such as the ministry, the port and the government. respective counties or cities.